Folheando espaços: caminhos de uma poética do cotidiano - Angela Santos de Andrade (2006)
Reflective analysis about the creation of drawings produced from1994 up to 2003, beginning of the specificity of their shapers elements. Recurrent aspects in my graphic language are show up, as the serial production, the employ of agglomerated papers as a support and also ofgraphic elements and materials in a concise and economic way. This study includes my looking over of the habitually spaces like house, city and nature. It presents thoughts about the production of three contemporary artists - Mira Schendel, Leonilson e Rochelle Costi - that denote similarities with my artistic examination in some aspects.